2022
DOI: 10.1038/s41598-022-10691-1
|View full text |Cite
|
Sign up to set email alerts
|

Tests of rubber granules used as artificial turf for football fields in terms of toxicity to human health and the environment

Abstract: Rubber waste, in the form of granules of styrene butadiene rubber and ethylene-propylene-diene-monomer with a particle size of 0.5 to 4 mm, is broadly used for the construction of synthetic surfaces of sport fields. This method of recycling may be significantly limited due to the restrictions on polycyclic aromatic hydrocarbons (PAHs) content in rubber granules in the European Union since 2022. This also applies to the recommendations of the European Chemicals Agency in relation to the identification of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Accurate testing is especially relevant for EPDM and ELT because they are not specific types of polymers such as PET or PP; in fact, they are umbrella terms for a wide array of substances with different chemical compositions. Missing scientific data/consensus from the field is a tremendous issue, particularly with ELT as 90% of all AT pitches use this material; e.g., Mohajerani et al and Armada et al highlight that the rubber contains toxic organic substances and metals which are known to leak, whereas Grynkiewicz-Bylina et al pointed out that at a neutral pH, no toxic leachates were observed [68][69][70]. Although there are studies that show no acute toxicity to aquatic species, those studies also remark that their results are preliminary, need further validation, and may not represent real aquatic conditions, a conclusion that is also drawn in the review by .…”
Section: Discussionmentioning
confidence: 99%
“…Accurate testing is especially relevant for EPDM and ELT because they are not specific types of polymers such as PET or PP; in fact, they are umbrella terms for a wide array of substances with different chemical compositions. Missing scientific data/consensus from the field is a tremendous issue, particularly with ELT as 90% of all AT pitches use this material; e.g., Mohajerani et al and Armada et al highlight that the rubber contains toxic organic substances and metals which are known to leak, whereas Grynkiewicz-Bylina et al pointed out that at a neutral pH, no toxic leachates were observed [68][69][70]. Although there are studies that show no acute toxicity to aquatic species, those studies also remark that their results are preliminary, need further validation, and may not represent real aquatic conditions, a conclusion that is also drawn in the review by .…”
Section: Discussionmentioning
confidence: 99%
“…Rubber granulate plates have good sound absorption and insulation properties [28]. Moreover, they are often used for the installation of artificial surfaces for sports grounds, tracks, and arenas [29]. This is the most common way of tire waste recovery, corresponding with the waste hierarchy and the principles of circular economy.…”
Section: Introductionmentioning
confidence: 99%
“…Tires are made from rugged, hard-wearing rubber, so disposing of them is a major environmental challenge. They cannot be easily recycled, are difficult to reuse, break down into crumbs causing an increase in the content of microplastics in the environment [1][2][3][4][5]. Pilkington [2] emphasizes that the United States alone disposes of 246 million to 300 million used tires each year.…”
Section: Introductionmentioning
confidence: 99%
“…This concrete will then be stored as demolition waste in landfills or used to strengthen the ground. black and 40 different chemicals, waxes, oils, pigments, silica and clays [1,[17][18][19][20]. According to ETRMA [19], tires contain an exemplary composition: rubber/elastomers (48%), carbon black (22%), metal (15%), additives (8%), textiles (5%), zinc oxide (1% passenger tires or 2% truck and off-road tyres), sulfur (1%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation